Micropropagation and in Vitro Flowering of Luffa acutangula (L.) Roxb.- an Important Vegetable Crop - Saha, Partha Sarathi; Ghosh, Biswajit (International Journal of Bio-resource and Stress Management, 2014)
An efficient protocol has been established for micropropagation and in vitro flowering of Luffa acutangula (L.) Roxb. in the present study. Maximum numbers of shoots (8.2±0.29/ nodal explants) were obtained in the MS medium supplemented with 4.44 μM of 6-Benzylaminopurine (BA). Doubling of 40 mM of FeSO4 and Na2EDTA resulted in chlorosis prevention of in vitro leaves. Nearly 100% of in vitro plants induced roots in presence of ½ MS medium containing 4.90 μM of IBA within 12.4±0.40 days of culture. Cytological analysis of the donor and regenerated plantlets revealed chromosome stability with 2n=26 chromosomes. About 100 % of the in vitro grown plants induced both male and female flower buds in MS medium (with 3% sucrose). Nearly 90.5% of the pollen grains formed in the in vitro male flowers were viable. The survival rate of acclimatized plants reached 94.5% when transferred to field conditions. Therefore, the present study can be considered as a promising system for efficient micropropagation and in vitro flowering of L. acutangula, which can also be a source of viable aseptic anthers, and thus can be directly used for haploid culture.